Instructional Observation of Positive Teacher Behavior Assessment Strategy in Elementary Classroom Activities - Margaret Stevani (International Journal of Language and Ubiquitous Learning, 2023)
Background. This study examined how positive teachers' behavior impacted young learners' engagement in elementary school. It focused on two main aspects: how well young learners followed instructions and how teachers delivered clear instructions during classroom activities. Purpose. The central question was whether observing positive teachers’ behaviors during instruction could boost young learners' participation.Using a descriptive qualitative approach, this research analyzed the structure of positive instructions, including direct commands, questions, statements, and clarification requests through observation and recording. This research involved 8 teachers from an International Elementary School in North Sumatra and 24 young learners. Method. To ensure the reliability of the findings, this research used content validity and inter-rater reliability. The results provided a specific measure for evaluating elementary teachers' instructional practices through observation. It highlighted their abilities to manage classroom transitions and provide clear guidance to young learners during activities that can positively impact their academic motivation. Results. This research conclude the constructive instruction of teachers in lesson teaching  by combining social, communication, and emotional regulation skills through by calculating young learners' participation scores.